BIOECOLOGY OF RODENTS OF THE LOWER AMU DARYA REGION - Adilbayeva Genjexan (Journal of Applied Science and Social Science, 2026)
This study investigates the bioecological characteristics of rodent species inhabiting the lower reaches of the Amu Darya. The research focuses on species diversity, habitat distribution, feeding ecology, and population dynamics under conditions of arid climate and increasing anthropogenic pressure. Field observations and ecological analyses demonstrate that rodent communities exhibit significant adaptive capacity to environmental stressors such as desertification, salinization, and habitat transformation. The study also highlights the ecological role of rodents as key components of trophic systems and bioindicators of ecosystem health. The results contribute to a deeper understanding of biodiversity patterns and provide a scientific basis for conservation and sustainable ecosystem management in the lower Amu Darya region.